Investigation of the hepatic respiration and liver zonation on rat hepatocytes using an integrated oxygen biosensor in a microscale device. (12th June 2019) - Matsumoto, Satomi; Safitri, Astia R.; Danoy, Mathieu; Maekawa, Toshiro; Kinoshita, Haruyuki; Shinohara, Marie; Sakai, Yasuyuki; Fujii, Teruo; Leclerc, Eric
Abstract: The development of an in vitro functional liver zonation model is a major issue to reproduce physiological liver features. Oxygen concentration is one of the potential explanations of a primary regulating factor of zonation. In this frame, we investigated the oxygen gradient inside a microfluidic device containing rat hepatocyte cultures. The device integrated a platinum (Pt) (II) octaethylporphyrin sensor, allowing a 2D mapping of the oxygen concentration. After 3 hr adhesion of the hepatocytes, the sensor indicated an intense oxygen depletion, leading to an oxygen shortage in the center of the device. After a 30 min perfusion of the culture medium, we monitored the formation of the oxygen gradient along the culture due to cellular respiration. The profile of the oxygen gradient was modulated and controlled by increasing either the perfusion flow rate or the device thickness. In addition, the oxygen gradient was time dependent as far as it decreased with the time of culture. Perivenous and periportal liver patterns were characterized by the immunostaining of the hepatic markers. We put in evidence a spatio temporal hepatic organization. We observed the overexpression since 24 hr of perfusion of the APC and PCK1 proteins upstream in the oxygen‐rich area of the device. The overexpression of GS, GCK, CYP1A, and HIFα proteins were observed downstream in the oxygen‐poor area. Then, CYP3A2 and β‐catenin spatial reorganization was achieved after 48 hr of culture. The results presented a partial zonation‐like pattern that was superimposed with an oxygen gradient profile.